F(h(x)) means wherever you see x in the f(x) function you're gonna plug in the h(x) function:
f(h(x)) = (2x + 3) - 7
= 2x + 3 - 7
= 2x - 4
Answer:
(- 4, - 10 )
Step-by-step explanation:
Given the 2 equations
y = x - 6 → (1)
x = - 4 → (2)
Substitute x = - 4 into (1) for corresponding value of y
y = - 4 - 6 = - 10
Solution is (- 4, - 10 )
Answer:
710
Step-by-step explanation:
if its wrong tell me (☞゚ヮ゚)☞(if it right plz give me brainlist)☜(゚ヮ゚☜)
Answer:
The value to be added to the polynomial x³ - 6·x² + 11·x + 8 so that it is completely divisible by 1 - 3·x + x² is -(x + 11)
Step-by-step explanation:
By long division, we have;
= x - 3
-(x³ - 3·x² + x)
-3·x² + 10·x + 8
-(-3·x² + 9·x -3)
x + 11
Therefore, -(x + 11) should be added to the polynomial x³ - 6·x² + 11·x + 8 so that it is completely divisible by 1 - 3·x + x².
That is (x³ - 6·x² + 11·x + 8 - x - 11) ÷ (1 - 3·x + x²) = x - 3.
Answer:
B. A small carton holds 6 eggs, and a large carton holds 8 eggs